Implementasi Kaidah Izā Ijtama’a al-Ḥalālu wa al-Ḥarāmu Gulliba al-Ḥarāmu dalam Menghadiri Walimah Bermusik Perspektif Hukum Islam: The Implementation of Izā Ijtama’a al-Ḥalālu wa al-Ḥarāmu Gulliba al-Ḥarāmu Principle in Attending Music-filled Walimah from Islamic Law Perspective (AL-FIKRAH: Jurnal Kajian Islam, 2025)
This research seeks to explore the Islamic perspective on the concept of walimah al-‘urs and the use of music within it, as well as to analyze the ruling on attending musical walimah events through the lens of the fiqh principle Izā Ijtama‘a al-Ḥalālu wa al-Ḥarāmu Ghuliba al-Ḥarām. The study employs a qualitative descriptive approach with a library-based method of data collection. The analysis is conducted using normative juridical methods, complemented by a conceptual framework. Data analysis is done qualitatively with the deductive method. The results show that the law of fulfilling walimah or wedding invitations is obligatory with several requirements. The prohibition of listening to music and playing musical instruments is supported by the aforementioned evidences. The law of fulfilling an invitation to a musical walimah is obligatory if the invitee is able to change the evil contained in the walimah, in this case music. However, if the invitee is unable to change the evil contained in the walimah, then the law is haram based on the rule of Izā Ijtama'a al-Ḥalālu wa al-Ḥarāmu Gulliba al-Ḥarāmu. This research is important as a guide for the community in dealing with the phenomenon of walimah involving music. By understanding the rules and Islamic law that apply regarding the issue of attending a musical walimah, people can make wiser decisions when faced with these problems.